Adult-Onset Tufted Angiomas Associated With an Arteriovenous Malformation in a Renal Transplant Recipient: Case Report and Review of the Literature. (February 2015) - Grassi, Sara; Carugno, Andrea; Vignini, Mariadelaide; Rosso, Renato; Borroni, Riccardo G.
Abstract : Abstract: Tufted angioma (TA) is a rare benign vascular neoplasm characterized histopathologically by the proliferation of endothelial cells arranged in lobules in the dermis and subcutaneous fat. To date, about 200 cases have been reported, most of which are of Japanese ethnicity. TA predominantly affects children and young adults, developing in 80% of patients younger than 10 years. A white 72-year-old renal transplant recipient presented with 2 asymptomatic dusky red papules on his right leg. The lesions appeared 5 years after the start of immunosuppressive treatment. Histopathologic examination showed a proliferation of poorly canalized capillary-sized vascular structures with typical "cannonball" pattern in the dermis and subcutaneous fat. Eccrine glands were also evident focally in the stroma of capillary lobules. On immunohistochemistry, endothelial cells in the vascular tufts stained positive for CD31 and CD34 but were negative for factor VIII-related antigen, human herpes virus 8, and podoplanin (clone D2-40); α-smooth muscle actin stained pericytes disposed in a single layer in capillary-sized vessels and in 2–3 or more layers in vessels of larger size, respectively. The microscopic findings were suggestive of TA. In the deep dermis, venules with smooth muscle wall and arterioles, as shown by Van Gieson staining, normally not found at that level, were present and appeared surrounded by capillary lobules. Onset of TA in adulthood is rare and may be associated with pregnancy, varicella zoster virus infection, and pharmacological immunosuppression. A case of acquired adult-onset TA associated with an arteriovenous malformation in an elderly transplanted patient is described.